Analisis Wacana Kritis Michel Foucault terhadap Representasi Kasus Bullying Timothy Anugrah Saputra dalam Podcast Denny Sumargo - Jelita Christy Sianipar; Enjelika Barus; Neni Lasinta Lumban Siantar; Indah Lestari Hasugian; Sarma Panggabean (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the construction of discourse, power relations, and the production of truth in a podcast discussing Timothy's case using Michel Foucault's Critical Discourse Analysis framework. The focus of the research lies in how power works through language, body, institutions, and discursive practices in shaping subjects and producing